Challenging the masculine story of the Fees Must Fall movement - Seabe, Busisiwe Cathrine (Rhodes University, 2026)
This thesis critically explores the often-disregarded contributions, marginalisations, and resistance towards Black radical feminist activists within the Fees Must Fall (#FMF) movement. The #FMF movement, which emerged in 2015, marked a pivotal moment in South Africa’s post-apartheid history, speaking to the deep-rooted inequalities embedded within the higher education system. Considering that ample attention has been placed on the movement's comprehensive political and economic demands – like the call for fee-free and decolonised education – this research accentuates the gendered dimensions of #FMF, highlighting how patriarchal structures sought to dominate the leadership, narratives and the activism of Black women involved in the movement. The study uses a transdisciplinary qualitative methodology, incorporating semi-structured interviews with Black female activists, and analyses the data through the lenses of intersectionality and Black radical feminism. The findings of the study identified five central themes, namely: the motivation that drew Black women to #FMF, the daily sexism they faced within the movement, the marginalisation of Black radical feminist perspectives, the silencing of women's voices in the official discourse of #FMF, and the strategies of resistance and resilience employed by Black feminists to confront these challenges. Notably, one such strategy was the establishment of feminist collectives like Mbokodo Lead, which presented women with free spaces to organise, assert leadership and critique the patriarchal structures entrenched within the movement itself. This study argues that #FMF can be seen as a microcosm of broader societal struggles, mostly reflecting the unresolved tensions within post-apartheid South Africa concerning race, class and gender. The analysis exposes how, while #FMF stood in opposition to the neoliberal commodification and colonial epistemic dominance in higher education, it often overlooked its own internalised patriarchal practices. Black radical feminist activists, however, challenged the “masculine story” of #FMF by reframing the movement within an intersectional lens that prioritised gender justice alongside the decolonisation of education. This study makes a noteworthy contribution to scholarship on decoloniality, intersectionality and feminist resistance by centring on the voices of Black women, whose roles have historically been marginalised in dominant narratives. It argues that the true decolonisation of education requires not only the dismantling of Eurocentric curricula but also the challenging of hetero-patriarchal power structures within activist movements and institutions. By positioning #FMF within the broader context of global grassroots struggles for justice, this study emphasises the movement's implications for reshaping activism, education and policymaking. In essence, this study calls for a reconceptualisation of movements like #FMF, ensuring that they are not only inclusive but also transformative. It insists that the fight for decolonised education and social justice must centre on the leadership and experiences of marginalised groups, especially Black women. It urges educators, activists, and policymakers to engage critically with the intersectional challenges posed by systemic oppression and presents a framework for creating movements that resist not only external inequalities but also internal exclusions. This research underscores the transformative potential of feminist resistance in reshaping activism and rethinking what it means to achieve equity and justice in a postcolonial world.
Keywords: Uncatalogued